Fungibility and the Flypaper Effect of Project Aid : Micro-Evidence for Vietnam - van de Walle, Dominique; Mu, Ren (World Bank, Washington, DC, 2012)
While most economists assume that aid is fungible, most aid donors behave as if it is not. The authors study recipient government responses to development project aid in the context of a specific World Bank-financed project. They estimate the impact of a rural road rehabilitation project in Vietnam on the kilometers of roads actually rehabilitated and built. Using local-level survey data collected for this purpose, the authors test whether the evidence supports the standard economic argument that there will be little or no impact on rural roads rehabilitated, given fungibility. They find evidence that, although project aid impacts on rehabilitated road kilometers were less than intended, more roads were built in project areas. The results suggest that there was fungibility within the sector, but that aid largely stuck to that sector.